The Use of PILA-Pack: Differences in Length of Stay of Hemorrhoidal Patients - Fadli Robby Amsriza; Rizka Fakhriani (Fakultas Kedokteran Universitas Brawijaya, 2022)
Hemorrhoids are a common anorectal disease and can affect all ages. This research aims to specify the differences in Length of Stay (LOS) of hemorrhoidal patients who underwent a modified combined method of rubber ligation and sclerotic injection using Paran Injection Ligation for Ambeien pack (PILA pack) compared to a hemorrhoidectomy. This study consisted of 56 respondents who underwent hemorrhoidectomy, and the other 56 respondents experienced a modified combined method of rubber ligation and sclerotic injection using a PILA pack. Data showed the LOS's average of respondents who underwent hemorrhoidectomy was 47.33 hours or 1.97 days. Meanwhile, respondents' average length of stay who underwent a modified combined rubber ligation and sclerotic injection using a PILA pack was 20.44 hours or 0.85 days. Finally, the T-test results showed a p-value of 0.001 (p<0.05), indicating that there was a statistically significant difference in the average LOS between hemorrhoidal patients who underwent hemorrhoidectomy and hemorrhoidal patients who underwent a modified combined method of rubber ligation and sclerotic injection using PILA pack. Based on the result, it can be concluded that the mean LOS for hemorrhoidal patients receiving haemorrhoidectomy vs. hemorrhoidal patients undergoing a modified technique of rubber ligation and sclerotic injection utilizing the Paran Injection Ligation for Ambeien pack was significantly different.